Light and Electron Microscopic Examination of Thyroid Parafollicular Cells in Pinealectomized Rats - Kuş, İlter; Öner, Hakan; Ögetürk, Murat; Kavaklı, Ahmet; Zararsız, İsmail; Sarsılmaz, Mustafa (Fırat University, 2003)
Aim : This study was aimed to examine thyroid follicular cells after pinealectomy at light and electron microscopic level. Materials and method: For this purpose, 12 male Wistar rats were divided into two groups. Rats in group I were used as control (sham-pinealectomy), whereas rats in group II were pinealectomized. At the end of the one-month experimental period, all rats were killed by vascular perfusion. The thyroid glands of animals were removed, then electron microscopic blocks of tissue specimens were prepared with routine histological procedures. Semi thin section obtained from electron microscopic blocks were stained with toluidine blue, and used for light microscopic examination. Thin sections were stained with lead citrate-uranil acetate and examined under an electron microscope. Results: In light microscopic examination, it was observed that hypertrophy of thyroid parafollicular cells after pinealectomy. Additionally, an increase in number of these cells was noticed. In electron microscopic examination, it was determined that increase of secretory granules in the cytoplasm of parafollicular cells. Conclusion: Increased of cell activity was seen in the thyroid parafollicular cells after pinealectomy.

Amaç: Bu çalışmada, pinealektomi sonrası tiroid parafolliküler hücrelerinin ışık ve elektron mikroskop düzeyde incelenmesi amaçlandı. Gereç ve yöntem: Bu amaçla, 12 adet Wistar albino cinsi erkek sıçan iki gruba ayrıldı. Grup I'deki sıçanlar kontrol (sham-pinealektomi) olarak kullanıldı. Grup II'deki sıçanlara ise pinealektomi yapıldı. Bir aylık deney süresi sonunda sıçanlar vasküler perfüzyonla öldürüldü. Bütün hayvanların tiroid bezleri çıkartılarak rutin histolojik yöntemlerle elektron mikroskobik blokları hazırlandı. Elektron mikroskobik bloklardan alınan yarı ince kesitler toluidin blue ile boyanarak ışık mikroskobik incelemeler için kullanıldı. Bloklardan alınan ince kesitler ise Kurşun sitrat-Uranil asetat'la boyanarak elektron mikroskobunda incelendi. Bulgular: Işık mikroskobik incelemelerde, pinealektomi sonrası tiroid parafolliküler hücrelerinde hipertrofi meydana geldiği gözlendi. Ayrıca, hücre sayısında da bir artışın olduğu dikkati çekti. Elektron mikroskobik incelemelerde ise, parafolliküler hücre sitoplazmalarındaki salgı granüllerinde artış olduğu belirlendi. Sonuç: Pinealektomi sonrası tiroid parafolliküler hücre aktivasyonunda artış meydana geldiği görüldü.
Pinealektomili Sıçanlarda Tiroid Parafolliküler Hücrelerinin Işık ve Elektron Mikroskop Düzeyde İncelenmesi